Visual Media On Language Learning: How Different Visual Aids Affect Comprehension And Retention - Tengku Fariqul Haq; Nur Zahra Madany (Yayasan pendidikan dzurriyatul Quran, 2025)
This study examines the impact of visual media, specifically infographics and images, on language learning among elementary students. Utilizing Mayer’s Cognitive Theory of Multimedia Learning as a framework, the research investigates how these visual aids enhance comprehension and retention of language material. The study employed a pre-experimental design with pre-tests and post-tests to measure students' performance after exposure to visual aids. Results revealed that infographics significantly outperformed images, showing a 31% improvement in comprehension and a 33% increase in retention, compared to 22.5% and 24%, respectively, for images. Infographics proved more effective due to their structured design, which integrates visual and textual elements to reduce cognitive load and facilitate better understanding of complex linguistic concepts such as grammar and sentence structure. Conversely, images were more effective for vocabulary acquisition but lacked the organization needed for teaching abstract language rules. These findings highlight the potential of well-designed visual media to improve learning outcomes and provide practical insights for educators aiming to create engaging and effective instructional methods.